Taxation and the Household Saving Rate : Evidence from OECD Countries - Zee, Howell (IMF Working Papers; Working Paper, 1998)
This paper analyzes anew the relationship between taxation and the household saving rate. On the basis of standard savings and tax revenue data from, it provides compelling and robust empirical evidence of a powerful impact of taxes on household savings. In particular, income taxes are shown to affect negatively the household saving rate much more than consumption taxes.